Diseminasi Tepung Mocaf Di Sungai Raya Kubu Raya - Yohana Sutiknyawati Kusuma Dewi; Dzul Fadly; Wisi Wilanda Syamsi; Brigita Ratna Harsanti (Universitas Andi Djemma, 2024)
The community service entitled Dissemination of Mocaf Flour in Sungai Raya Kubu Raya was carried out with the target audience of BPP Sungai Raya workers and the members of the Haji Ali 1 farmer group in Kuala Dua village. The problems faced by the lack of knowledge and skills in post-harvest handling of cassava into mocaf and how to test the flour quality. The solution offered is the diffusion of technology for making mocaf flour as a choice in the production aspect, while for the management aspect the solution offered is a quality assurance system by training community representatives by conducting product quality tests as a result of assistance in the food design laboratory of the Faculty of Agriculture, Tanjungpura University. The target achieved from this activity was to increase knowledge to 60% about mocaf flour and there were at least 3 participants who came from extension workers or members of the Haji Ali 1 farmer group who were skilled at making mocaf and had knowledge of the quality of mocaf at least 60%. The benefit of this community service is to increase the competitiveness of Human Resources in the Kuala Dua village and BPP Sungai Raya Kubu Raya workers.